Indícios de autoria: Escrita e reescrita de textos em contexto escolar - Silva, Ingrid Liliam da (2023)
In view of the need for new studies concerning the teaching of Portuguese Language in Basic Education, this research seeks to investigate, focusing on the stage of High School, issues that contribute to the practice of writing and rewriting texts in school. In order to develop an analytical-discursive investigation that allows reflections on the theme, we will base ourselves on Possenti (2001, [2002] 2009), who postulates the notion of evidence of authorship; in Geraldi (1991), which presents ways to consider the conditions of production of a text, especially in the school context; in Fiad (2013), which conceives of writing as work; in Bakhtin ([1992] 2000), which presents the notion of gender of the discourse that we will use; in Mussalim (2020), according to which the field of human activity in which genres are produced and circulated, and not the genres of discourse itself, should be the organizing center of the Portuguese Language curriculum. The hypothesis that guided the present research is that we can find evidence of authorship (POSSENTI, 2009) in texts produced by students in a school context, especially when the work with writing includes the work with rewriting (FIAD, 2013). The analytical procedure, therefore, implied a comparison between the first textual production of each student and its subsequent rewriting, based on the corpus collected during the course "Genres of discourse of the journalistic field: reading and production of texts", taught by members of the Research Group Círculo de Estudos do Discurso (CED) in the year 2021. To perform the analyses, we selected from a total of 14.6 pairs of texts (Production 1 and Rewriting of each student), in order to verify to what extent the process of rewriting texts enabled and/or optimized the appearance of evidence of authorship that, according to Possenti (2013), are related to the attitudes of giving voice to other enunciators; keep your distance from the text itself; and avoid sameness. As the results suggest, there is evidence both of the productivity of working with the genres of discourse in the school environment, starting from the understanding of the functioning of the field of activity in which the genres are produced and circulated, and that the rewriting process enables and/or optimizes the appearance of evidence of authorship in school texts. With this research, we hope to contribute to the understanding of the inextricably of the relationship between sphere-gender (MUSSALIM, 2020); to make visible the need to adequately work on the conditions of text production in the classroom; and to raise awareness of the need to include the work of rewriting texts as one of the core elements of the Portuguese Language curriculum.